2017
DOI: 10.21037/jtd.2017.06.19
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of lymph node metastases of squamous cell esophageal cancer based on the anatomical lymphatic drainage system: efficacy of lymph node dissection according to tumor location

Abstract: Knowing the anatomical lymphatic drainage of the esophagus is crucial to understanding the dissemination pattern of esophageal tumor. During the embryonal growth, the middle and lower part of the esophagus stretches as the lymphatic networks develop in the submucosal layer. The abundant submucosal lymphatics drain in a longitudinal fashion directly to their proximal and distal ends. The lymphatic route from the proximal esophagus through recurrent nerve nodes to supraclavicular nodes are a component of the mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…A rich lymphatic network is present in the LP and is further concentrated in the SM. Several studies had suggested that lymphatics within the SM drains longitudinally along the submucosal plexuses up to its proximal ends (recurrent laryngeal nodes/supraclavicular node) or down to its distal ends (paracardial nodes/celiac nodes), bypassing the network in MP/adventitia and regional LNs. Direct drainage into the thoracic duct has also been documented in autopsy studies .…”
Section: The Submucosamentioning
confidence: 99%
“…A rich lymphatic network is present in the LP and is further concentrated in the SM. Several studies had suggested that lymphatics within the SM drains longitudinally along the submucosal plexuses up to its proximal ends (recurrent laryngeal nodes/supraclavicular node) or down to its distal ends (paracardial nodes/celiac nodes), bypassing the network in MP/adventitia and regional LNs. Direct drainage into the thoracic duct has also been documented in autopsy studies .…”
Section: The Submucosamentioning
confidence: 99%
“…In this context, recurrent nerve lymph nodes are well known as frequent metastasis sites of thoracic esophageal squamous cell carcinoma . This is related to the submucosal lymphatic vessels running longitudinally along the thoracic esophagus, directly draining into the proximal and distal ends and consequently connecting the recurrent nerve and perigastric lymph nodes . Therefore, the locations of lymph node metastasis of SESCC exhibit a unique distribution to the recurrent nerve or perigastric lymph nodes, which can involve a solitary lymph node .…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] This is related to the submucosal lymphatic vessels running longitudinally along the thoracic esophagus, directly draining into the proximal and distal ends and consequently connecting the recurrent nerve and perigastric lymph nodes. 25 Therefore, the locations of lymph node metastasis of SESCC exhibit a unique distribution to the recurrent nerve or perigastric lymph nodes, which can involve a solitary lymph node. 12,21,24,26 The perigastric lymph nodes are also known as frequent metastasis sites, especially for middle and lower thoracic esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Local relapse and regional lymphatic metastasis are important causes of failure after radical resection and irradiation of ESCC, leading to poor survival rates . Regional lymphatic metastasis of ESCC involves a wide region from the neck to the upper abdomen . Because of this pattern of lymphatic metastasis, it is difficult to remove and irradiate all regional lymph nodes via radical resection and irradiation, which can also have severe implications.…”
Section: Discussionmentioning
confidence: 99%